The relationship between gut microbiota and insomnia: a bi-directional two-sample Mendelian randomization research - Li, Yan; Deng, Qingqing; Liu, Zhanli (Frontiers in Cellular and Infection Microbiology, 2023)
Insomnia is the second most common mental health issue and a social and financial burden. Insomnia affects the balance between sleep, the immune system, and the central nervous system, which may raise the risk of different systemic disorders. The gut microbiota, referred as the "second genome," has the ability to control host homeostasis. It has been discovered that disruption of the gut-brain axis is linked to insomnia. In this study, we conducted MR analysis between large-scale GWAS data of GMs and insomnia to uncover potentially association. 10 GM taxa were detected to be causal associations on insomnia. Among them, class Negativicutes, genus Clostridiuminnocuumgroup, genus Dorea, genus Lachnoclostridium, genus Prevotella7 and order Selenomonadalesare are linked to a higher risk of insomnia. In reverse MR analysis, we discovered a causal link between insomnia and six other GM taxa.It suggested that the relationship between insomnia and intestinal flora is convoluted. Our research could help identify disease-related biomarkers and potential targets for treating insomnia.